1997
DOI: 10.1006/qres.1996.1866
|View full text |Cite
|
Sign up to set email alerts
|

Astronomical Forcing of Contrasting Rainfall Changes in Tropical South America between 12,400 and 8800 cal yr B.P.

Abstract: Today, precipitation over tropical South America is largely controlled by the seasonal movements of the Inter-Tropical Convergence Zone (ITCZ). During the summer, the ITCZ is shifted southward due to the warming of the continent. Paleoclimate data from southeastern Amazonia and the central Andes indicate that these two areas evolved similarly during the last 30,000 yr. However, between 12,400 and 8800 cal yr B.P., eastern Amazonia received substantial moisture whereas the Bolivian Altiplano was arid. This sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0
11

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(96 citation statements)
references
References 23 publications
7
78
0
11
Order By: Relevance
“…This means that the record presented here started at the beginning of the Holocene, at the Pleistocene/Holocene boundary, when climate was recorded as humid, similar to present. This agrees with the main picture established for Venezuela and also for savanna areas located northward the ITCZ (Martin et al 1997). In Mapire core, the Early Holocene humid period lasted from 10,225 yr BP to 7,800 interpolated yr BP.…”
Section: Comparison With Other Records From Venezuela and Northern Sosupporting
confidence: 90%
“…This means that the record presented here started at the beginning of the Holocene, at the Pleistocene/Holocene boundary, when climate was recorded as humid, similar to present. This agrees with the main picture established for Venezuela and also for savanna areas located northward the ITCZ (Martin et al 1997). In Mapire core, the Early Holocene humid period lasted from 10,225 yr BP to 7,800 interpolated yr BP.…”
Section: Comparison With Other Records From Venezuela and Northern Sosupporting
confidence: 90%
“…Martin et al (1997) suggests that during the mid-Holocene, the ITCZ was located farther north than its present-day position (Fig. 1) this would produce a summer rainfall deficit and increased winter precipitation; in short greater seasonality.…”
Section: ±500 14 C Yr Bpmentioning
confidence: 97%
“…One of the main mechanisms used to explain moisture shifts is fluctuations in the Southern Oscillation and the migration of the ITCZ (Martin et al, 1997). Martin et al (1997) suggests that during the mid-Holocene, the ITCZ was located farther north than its present-day position (Fig.…”
Section: ±500 14 C Yr Bpmentioning
confidence: 99%
“…13,000}10,000 BP) there is a sudden increase in temperature and rainfall, and most lake levels rise around 12,500 BP, especially in the tropics (Martin et al, (1997) showed a valuable concept on astronomical forcing of South American rainfall). There is a short, cold interval between 11,000 and 10,000 BP (Younger Dryas stadial), locally also somewhat drier, and 10,000 BP is the beginning of the Holocene.…”
Section: The Last Glacial Climatic Sequencementioning
confidence: 99%